Tales from the Masnavi - "Arberry, A.J." (London, 1961)
The Masnavi I Ma'navi of Rumi is one of the most influential works of Sufism, commonly called "the Quran in Persian". It has been viewed by many commentators as the greatest mystical poem in world literature. Its diversity, complexity and profoundness, the timeless themes of power, God, love and fidelity, together make the MASNAVI one of the most compelling and memorable spiritual works of world literature. Its author, the Persian poet and Sufi mystic, Maulana Jalalu-'d-din Muhammad Rumi (1207-1273), found his own religious order, the Whirling Dervishes. To many modern Westerners, this series of six books of poetry, translated by E. H. Whinfield, is one of the best introductions to the philosophy and practice of Sufism. These poems are plenty of very profound thought, and you will not leave this fantastic work without spiritual growth.
Keywords: Religion